2007
DOI: 10.1021/jp0651236
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Iron Phase in CNx-Based Oxygen Reduction Reaction Catalysts

Abstract: Catalysts for the oxygen reduction reaction were prepared from the pyrolysis of acetonitrile at 900 °C over iron particles on various supports. The iron phases present in the active materials were characterized by XRD, TEM, and Mössbauer spectroscopy. Typically, the iron particles were encased in carbon after pyrolysis, explaining how they could survive subsequent acid washes. The Fe phases present included metallic gamma iron, cementite, and two oxidized phases. Although the relative abundance of the phases v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
97
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 46 publications
8
97
0
2
Order By: Relevance
“…These metallic particles are predominantly located at the base of the nanotubes, on its tip or encased inside them and entrapped within the graphene layers or covered by thin layers of amorphous carbon. They may exhibit electrocatalytic effects 29 and redox activity or even dissolve and show electrochemical activity in solution 30 depending on the supporting electrolyte composition, as was demonstrated by J. L. Lyon el at 31 . The electrodic process observed occurs at the potential expected for the Fe 3+ /Fe 2+ reaction in sulfuric acid 32 .…”
Section: -Results and Discussionmentioning
confidence: 88%
“…These metallic particles are predominantly located at the base of the nanotubes, on its tip or encased inside them and entrapped within the graphene layers or covered by thin layers of amorphous carbon. They may exhibit electrocatalytic effects 29 and redox activity or even dissolve and show electrochemical activity in solution 30 depending on the supporting electrolyte composition, as was demonstrated by J. L. Lyon el at 31 . The electrodic process observed occurs at the potential expected for the Fe 3+ /Fe 2+ reaction in sulfuric acid 32 .…”
Section: -Results and Discussionmentioning
confidence: 88%
“…5b could be assigned to pyridinic-N, quaternary-N and pyridinic-N + -O À , respectively. 28,35,38,56 As shown in Fig. 5c, the C1s peak of N-CX sample becomes wider than that of CX sample.…”
mentioning
confidence: 80%
“…[10][11][12][13][14] In order to decrease the cost of electrocatalysts and eliminate their dependence on noble metals, various non-noble metal catalysts have been explored recently as alternatives to the Pt-based electrocatalysts, which include chalcogenide catalysts, [15][16][17][18][19] transition metal macrocyclic compounds, [20][21][22] transition metallic oxides [23][24][25][26][27] and carbon-based catalysts. [28][29][30][31][32][33][34][35] In particular, carbon-based catalysts doped with the heteroatoms such as nitrogen (N) or boron (B) have been paid much attention and been proposed as typical non-noble metal catalysts for ORR [36][37][38] in alkaline media. Especially, since Gong et al 37 reported the superior activity and stability of nitrogen doped carbon nanotube in alkaline solution, the heteroatom doped carbon materials have been expected to be promising alternative Pt-based catalysts.…”
mentioning
confidence: 99%
“…Besides, heat-treated metal (Fe or Co)-N/C systems as another kind of non-Pt cathode catalyst have been under development for several decades [13][14][15], starting with the pioneer works by Jasinski [16] and by Yeager and co-workers [17]. Recently much progress has been made in this system [18][19][20][21].…”
mentioning
confidence: 99%